Nucleotide sequence of the fadR gene, a multifunctional regulator of fatty acid metabolism in Escherichia coli. - DiRusso, C C (1988)
The Escherichia coli fadR gene is a multifunctional regulator of fatty acid and acetate metabolism. In the present work the nucleotide sequence of the 1.3 kb DNA fragment which encodes FadR has been determined. The coding sequence of the fadR gene is 714 nucleotides long and is preceded by a typical E. coli ribosome binding site and is followed by a sequence predicted to be sufficient for factor-independent chain termination. Primer extension experiments demonstrated that the transcription of the fadR gene initiates with an adenine nucleotide 33 nucleotides upstream from the predicted start of translation. The derived fadR peptide has a calculated molecular weight of 26,972. This is in reasonable agreement with the apparent molecular weight of 29,000 previously estimated on the basis of maxi-cell analysis of plasmid encoded proteins. There is a segment of twenty amino acids within the predicted peptide which resembles the DNA recognition and binding site of many transcriptional regulatory proteins.